Corporate Debt Financing and Earnings quality - Wang, Lingqing (2017)
Debt financing is an important source to raise external funds and almost universally exists in each firm. Many studies explore the relationship between debt financing and earnings quality, however, the results are typically mixed. To examine the relation between debt financing and earnings quality, I select a sample of UK firms over the period 2006 to 2016 and find a non-monotonic relation between debt financing and earnings quality. Debt financing is positively related to earnings quality for low debt levels as mangers are willing to lower financing costs by improve earnings quality. But debt financing is negatively related to earnings quality for high debt levels since managers are likely to manage earnings to avoid debt covenant violations.